IMPORTANT INDICATORS AFFECTING INTEREST OF TAXPAYER BEHAVIOR USING E-FILING - Ida Ayu Oka Martini; I Gusti Ayu Wirati Adriati (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2020)
The problem that is always faced by taxpayers in the process of preparing and submitting Tax Returns (SPT) is the form of forms that often change and the length of queues when reporting SPT at the Tax Office. This causes taxpayers to be reluctant to prepare and report the SPT. The purpose of this study is to determine the security and confidentiality, readiness of information technology, perceptions of usefulness, perceptions of convenience, and perceptions of convenience affect the behaviour interest of taxpayers to use e-filing. The data collection technique used a questionnaire. with data analysis using regression analysis techniques. The results show that first, the indicators of Security and Confidentiality, Information Technology Readiness, Perception of Usability, Perception of Convenience, and Perceptions of Convenience simultaneously have a significant effect in increasing the behaviour of individual taxpayers to use e-filing at the Pratama East Denpasar Tax Service Office (KPP), Second, the indicators of Security and Confidentiality, Perception of Usability, Perception of Convenience, and Perceptions of Convenience have a significant effect on the behaviour of individual taxpayers to use e-filing at the Pratama East Denpasar Tax Service Office (KPP) Meanwhile, the Information Technology Readiness indicator has no significant effect on the behaviour interest of individual taxpayers to use e-filing at the Pratama East Denpasar Tax Service Office (KPP). Third, the Perceived Usefulness indicator has the most dominant influence in increasing the behaviour interest of individual taxpayers to use e-filing at the Pratama East Denpasar Tax Service Office (KPP).